2022
DOI: 10.1097/mco.0000000000000878
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiome in normal ageing, frailty and cognition decline

Abstract: Purpose of reviewThe intestinal microbiome modulates the risk of several age-related chronic diseases and syndromes, including frailty and neurodegenerative diseases. Herein we provided an update on the influence of gut microbiota on physical and cognitive performance in older age and suggest microbiota-targeted interventions for healthy ageing. Recent findingsLow uniqueness index of the gut microbiome and high representation of Bacteroides are independently associated with mortality in older individuals, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…These findings highlight the bidirectional relationship between gastrointestinal disorders and psychological well‐being, emphasizing the importance of addressing both aspects in treatment approaches. To evaluate this relationship, a clinical study by Strasser and Ticinesi (2023) assessed the effectiveness of cognitive‐behavioral therapy (CBT) in reducing both gastrointestinal symptoms and psychological distress in patients with IBS. The study found that CBT significantly improved both the severity of gastrointestinal symptoms and psychological well‐being, suggesting that addressing psychological factors can positively impact gastrointestinal disorders.…”
Section: Decoding the Roots: Understanding The Drivers Of Psychologic...mentioning
confidence: 99%
“…These findings highlight the bidirectional relationship between gastrointestinal disorders and psychological well‐being, emphasizing the importance of addressing both aspects in treatment approaches. To evaluate this relationship, a clinical study by Strasser and Ticinesi (2023) assessed the effectiveness of cognitive‐behavioral therapy (CBT) in reducing both gastrointestinal symptoms and psychological distress in patients with IBS. The study found that CBT significantly improved both the severity of gastrointestinal symptoms and psychological well‐being, suggesting that addressing psychological factors can positively impact gastrointestinal disorders.…”
Section: Decoding the Roots: Understanding The Drivers Of Psychologic...mentioning
confidence: 99%
“…Nevertheless, despite the limitations of studies published heretofore, there is a consensus that patients with MCI or dementia have a different fecal microbiota composition compared to healthy controls [ 69 ]. Secondly, in most, although importantly, not all studies, AD and MCI patients exhibit reduced representation of bacterial taxa producing SCFAs, and increased representation of Bacteroidetes [ 70 , 71 ] .…”
Section: Clinical Relevance Of the Gut–brain Axis In Dementiamentioning
confidence: 99%
“…In this scenario, frailty has started to be an urgent concern in a soon-to-beageing society. To date, several recent studies have suggested an involvement of the gut microbiota in the pathophysiology of frailty [8,28,29] (see also Table 1). Furthermore, a cross-sectional analysis in a community-dwelling cohort of 728 female twins found that a high frailty index was associated with reduced levels of SCFA-producing microbes with anti-inflammatory properties, such as Faecalibacterium prausnitzii, and increased proportions of proinflammatory members of the Enterobacteriaceae family [30].…”
Section: The Relationship Between Gut Microbiota and Frailty Syndromementioning
confidence: 99%
“…In this context, the debate is still open on whether changes in the gut microbiota profile during ageing (which encompasses the main factors listed earlier) are to be considered dysbiosis or vice versa adaptation to the aged condition, also considering the recent identification of potential longevity signatures in the microbiota of extremely long-lived people [7]. However, it remains a fact that particularly unbalanced gut microbial profiles can be established in the elderly, which have been associated with the onset and progression of age-related disorders, one of which is frailty syndrome [8] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%